O “calcanhar de Aquiles” da iniciação à vida cristã - Susin, Luiz Carlos (Revista Eclesiástica Brasileira, 2019)
Este artigo examina a atual condição da iniciação para a vida cristã no seio de uma sociedade com estruturas secularizadas e pluralismo religioso. Analisa a diferença e a distância entre a comunidade cristã e a sociedade em seu entorno, e os impasses de uma formação para a comunidade sem a correspondente formação para a vida cidadã, ou seja, para a formação à vida adulta como cristão e como cidadão responsável. O processo de iniciação levaria hoje a uma pertença infantil à comunidade ou a um dualismo insustentável cujo resultado é a desistência. Recorrendo ao dinamismo antropológico do rito de passagem de iniciação à vida adulta, o autor sugere uma atualização do mesmo em termos de sociedade atual por parte do cristão, insistindo em contatos, riscos, provas e treinos junto aos porões e margens da sociedade como parte da pedagogia preparatória para os sacramentos da Primeira Eucaristia e sobretudo Crisma. Abstract: This article examines the present condition of the initiation to the Christian life in the midst of a society with secularized structures and a religious pluralism. It analyses the difference and the distance between the Christian community and the society around it, and the impasses of a development of this community without an equivalent development towards a civil life, that is, the development of an adult life as a Christian and as a responsible citizen. The process of initiation nowadays would lead to a type of childlike belongingness to the community or to an unsustainable dualism the result of which is desistance. Resorting to the anthropological dynamism of the rite of passage to adult life, the author suggests an updating of the same in terms of the present society by the Christians, insisting in contacts, risks, proofs and training in the holds and margins of the society as part of the preparatory pedagogy for the sacraments of the First Holy Communion and in particular of the Confirmation. Keywords: Rite of passage; Initiation; Evidences; Trainings.